Droids everywhere! - Baker, Liza; Vanderstelt, Jerry (Scholastic New York, 2000)
Droids Everywhere! . is an engaging children$1 (Bs book that introduces young readers to the fascinating world of robots and droids. The story follows various droids as they navigate different environments, showcasing their unique functions and abilities$1 (Bfrom helpful household robots to advanced machines in space. Through vibrant illustrations and lively text, the book captures the imagination of children, encouraging them to explore technology and creativity. With its fun and educational approach, Droids Everywhere! aims to inspire an interest in robotics and innovation while entertaining young audiences.s